Variation in soil nitrous oxide emission with nitrogen application rates under reclaimed water irrigation - Chi, Yanbing; Wei, Chenchen; Yang, Peiling (Frontiers in Environmental Science, 2025)
Nitrous oxide (N2O) is a potent greenhouse gas primarily emitted from agricultural soils through microbial nitrogen transformation processes. Different nitrogen application rates and fertilizer types influence soil nitrogen transformation pathways, thereby affecting N2O production and emissions. Reclaimed water (RW), due to its chemical composition, may further modulate these processes. In this study, a disturbed soil incubation experiment was conducted using two irrigation water types [RW and deionized water (CW)], three nitrogen fertilizer forms [ammonium sulfate (NH4+), potassium nitrate (NO3−), and sodium nitrite (NO2−)], and two nitrogen application rates (200 and 400 mg N kg−1) to examine the dynamics of soil N2O emissions. The study found that, compared to CW, high fertilization levels (400 mg N kg−1) of NH4+ under RW treatment significantly increased cumulative soil N2O emissions by 25.04%, primarily by enhancing the abundance of the ammonia monooxygenase gene in ammonia-oxidizing archaea (AOA-amoA), the ammonia monooxygenase gene in ammonia-oxidizing bacteria (AOB-amoA), and the nitrite reductase gene (nirS). However, at low fertilization levels (200 mg N kg−1) of NH4+, there is no significant differences in cumulative N2O emissions. Under NO3− treatment, although RW increased the abundance of AOA-amoA and AOB-amoA, it did not lead to higher soil NO or N2O emissions at either high or low NO3− concentrations. In contrast, under NO2− treatment, RW increased the abundance of AOA-amoA and AOB-amoA compared to CW, significantly enhancing cumulative soil N2O emissions by 27.56% and 39.25%, respectively. In conclusion, RW irrigation does not elevate soil N2O emissions with nitrate-based fertilizers. However, careful management of nitrification rates is required with ammonium-based fertilizers, including the use of nitrification inhibitors and improved soil aeration, to minimize NO2− accumulation and related environmental risks.